Critic's Choice Essay: Cedar-apple Rust - Clark L. Ovrebo (Oklahoma Native Plant Record, 2006)
The photograph on the cover illustrates a phenomenon of nature that can be seen in the Oklahoma springtime at about the same time that the redbuds are in flower and the morels are fruiting. The orange-colored masses represent a stage in the life cycle of cedar-apple rust, Gymnosporangium juniperi-virginianae, and this stage is occurring on the eastern red cedar (Juniperus virginiana).